USAGE OF FLUTTER FRAMEWORK IN DESIGN AND DEVELOP MLEARNING APPLICATION AND ITS EFFECTIVENESS ANALYSIS AMONG WORKERS IN BATAM CITY - Syaeful Anas Aklani; Kelvyn (UNIVERSITAS STEKOM, 2023)
Changes or additions of new employee in a company is a normal thing and can be happen anytime. The process of training and introducing to new employee is the initial stage carried out by company after accepting new employee, this process is called onboarding. This research aims to designing and developing mobile application that is used to train and introduce for new employee. The application is developed with RAD (Rapid Application Development) method and using flutter framework along with firebase as the data storage. This research also doing analysis to the effectiveness usage of the mobile application developed with TAM (Technology Acceptance Model) model. Variables that is used in the analysis are Perceived Ease of Use, Perceived Usefulness, and Attitude Towards Using. Sample of this research is all workers in the Batam city. The research method is quantitative and analyze with regression using SPSS application. This research proves that mobile application can be used to conduct employee training.